Migration, citizenship, and the European welfare state a European dilemma - Schierup, Carl-Ulrik.; Hansen, Peo.; Castles, Stephen; Oxford eBooks (Oxford : Oxford University Press, 2006)
Linking two discourses which are normally viewed separately - research on ethnic relations and immigration and the political economy of the welfare state, the authors scrutinise one of Europe's most pressing predicaments - how to integrate processes at the local and national level with those at the supra-national level.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Welfare state -- Europe; Citizenship -- Europe; Europe -- Emigration and immigration; Europe -- Ethnic relations; Electronic books